If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -9)(x + 4) = 0 Reorder the terms: (-9 + 3x)(x + 4) = 0 Reorder the terms: (-9 + 3x)(4 + x) = 0 Multiply (-9 + 3x) * (4 + x) (-9(4 + x) + 3x * (4 + x)) = 0 ((4 * -9 + x * -9) + 3x * (4 + x)) = 0 ((-36 + -9x) + 3x * (4 + x)) = 0 (-36 + -9x + (4 * 3x + x * 3x)) = 0 (-36 + -9x + (12x + 3x2)) = 0 Combine like terms: -9x + 12x = 3x (-36 + 3x + 3x2) = 0 Solving -36 + 3x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-12 + x + x2) = 0 Factor a trinomial. 3((-4 + -1x)(3 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-4, 3}
| 4y+228=52 | | 12a-24=12 | | 3x+4(x+3)=68 | | 3x-8+x+12=17 | | -15*5/3c*8 | | -5(2x-1)=3(x+5) | | 56y+1=781 | | 6x+8=290 | | -3+1=x+9-4x | | v/4-10=5 | | 1.5x-18=0.5x | | 22/11x9-3 | | -4/3+x2+1/3x-8+8/3x | | 5v^2=20 | | 2/63/6= | | (2r-4s+6t)(2r-4s+6t)= | | 5y+y-9=8y+1 | | 4+12/4-2 | | 80x^2=50 | | 3(a-5)=6a(3a+15) | | -4/3+t2+1/3t-8+8/3t | | (a/6)-11=25 | | (3xy^2)(-5x^3y)= | | 4x-25x^1/2+25=0 | | 8x-36=8 | | ax-bx=-cforx | | -20c+3-3c+13= | | x-.20=64 | | 6.8x-4.7=17.62 | | 4x-25x^1/2+25 | | -12x+4-6x=2x+7x-3 | | -5b+24=-17+2x |